DNA-binding studies of mixed ligand cobalt(III) complexes - Barve, A. C.; Ghosh, Smita; Kumbhar, A. A.; Kumbhar, A. S.; Puranik, Vedavati G. (Transition Metal Chemistry, 2005)
The DNA binding characteristics of mixed ligand complexes of the type [Co(en)(2)(L)]Br-3 where en = N,N'-ethylenediamine and L = 1,10-phenanthroline (phen), 2,2'-bipyridine (bpy), 1,10-phenanthroline-5,6-dione (phendione), dipyrido[3,2-a:2',3'-c]phenazine (dppz) have been investigated by absorption titration, competitive binding fluorescence spectroscopy and viscosity measurements. The order of intercalative ability of the coordinated ligands is dppz > phen > phendione > bpy in this series of complexes.